Oxidative post-translational modification of EXECUTER1 is required for singlet oxygen sensing in plastids - Vivek Dogra (Nature Portfolio, 2019)
Singlet oxygen generated by photosynthesis under photo-oxidative stress conditions triggers retrograde signaling from plastids to nuclei. Here, the authors show that singlet oxygen perception and subsequent signaling events require oxidative post-translational modification of the EXECUTER1 protein.